Discrete event simulation for the investment analysis of offshore wind manufacturing processes. (23rd March 2022) - Lamas-Rodríguez, Adolfo; Taracido-López, Inés; Pernas-Álvarez, Javier; Tutor-Roca, Santiago-José
Spreadsheets are by far the most widely employed tool to perform investment analysis. However, in operations research, its rigidness ignores the variability inherent to stochastic systems and neglects important factors that may affect the feasibility of the investment. Hence, we present here an innovative use of discrete event simulation (DES) for investment analysis by means of two case studies taken from the offshore wind industry. To do so, we implemented an algorithm on top of a 3D DES model which performs the investment analysis in parallel with it. Results are shown by means of net present value (NPV) and internal rate of return (IRR). In this way, we consider at once process variability and variable economic factors like discount rate thus achieving more reliable results. Finally, we set investment parameters as target variables in the optimiser to obtain the best scenario regarding both productivity and profitability.